2018
DOI: 10.1115/1.4040864
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Loss Generation Mechanisms Inside Different Centrifugal Compressor Volutes for Turbochargers

Abstract: In centrifugal compressor design, the volute plays a key role in defining the overall efficiency and operating range of the stage. The flow at the impeller outlet is indeed characterized by a high kinetic energy content, which is first converted to potential energy in the diffuser downstream. The compressed gas is then collected by the volute at the cylindrical outlet section of the diffuser and directed to the intake piping, possibly with a further pressure recovery to enhance the stage performance. Due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The increase in the meridional velocity increases the swirl velocity in the volute, which causes the swirl-induced pressure losses as explained and reported by Hagelstein et al 12 Figure 17(c) shows reduction of total pressure in the volute core region because of the higher swirl velocity and turbulence, which leads to higher core vortex shear to produce total pressure loss. 35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the meridional velocity increases the swirl velocity in the volute, which causes the swirl-induced pressure losses as explained and reported by Hagelstein et al 12 Figure 17(c) shows reduction of total pressure in the volute core region because of the higher swirl velocity and turbulence, which leads to higher core vortex shear to produce total pressure loss. 35…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the meridional velocity increases the swirl velocity in the volute, which causes the swirlinduced pressure losses as explained and reported by Hagelstein et al 12 Figure 17(c) shows reduction of total pressure in the volute core region because of the higher swirl velocity and turbulence, which leads to higher core vortex shear to produce total pressure loss. 35 Figure 18 shows the comparison of wall shear stress (WSS) for different levels of volute roughness at the NC operating point with the design and off-design speeds. The area-averaged WSS predicted on the volute surface is normalized by the WSS value obtained at the NC operating point for the baseline housing at the design speed (N).…”
Section: Effect Of Volute Roughness Level On Flow Characteristicsmentioning
confidence: 99%
“…The increase in the meridional velocity and turbulence leads to higher core vortex shear in the volute. Tanganelli et al 28 showed that the volute core vortex flow produced higher total pressure losses which resulted in low-pressure regions.…”
Section: Part I: Effect Of Different Surface Roughness Level On Volutementioning
confidence: 99%
“…A CFD investigation on the compressor volute with different volute tongues and shapes showed that the total pressure losses were equal to the sum of the tongue and secondary vortex shear generated pressure losses in the volute. 28 Liu et al 29 numerically studied the effects of increase in blade roughness and showed that the compressor working range was reduced in the choke region but increased in the surge region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, an improvement of the volute performance or of any loss modelling is only possible on the basis of the knowledge gained from a numerical 3D analysis, which requires an enormous amount of computational effort due to the relative size of the volute in comparison to other components as well as the lack of axisymmetry. The publications of "Ayder and Van den Braembussche (1994)", " Gu et al (2001)", "Heinrich and Schwarze (2016)" and " Tanganelli et al (2018)" underline the importance of the numerical analysis regarding the volute to understand and assess occurring effects within the volute. The present work provides further insights with respect to the complex volute flow, in which sources of irreversibilities are identified and analyzed on the basis of a local entropy production analysis and compared against standard methods used to evaluate the volute performance.…”
Section: Introductionmentioning
confidence: 99%